ENDOMETRIOSIS AND EARLY DIAGNOSIS AND NEW APPROACHES TO TREATMENT (International Seven Journal of Health Research, 2025)
Endometriosis and uterine fibroids are common gynecological conditions that affect millions of women of reproductive age. Both conditions have a significant impact on quality of life and are associated with symptoms such as chronic pelvic pain, infertility and menstrual changes. This review article looks at advances in early diagnosis, highlighting the role of imaging tests, such as ultrasound and magnetic resonance imaging, and biological markers in the management of these conditions. It also explores new therapeutic approaches, including pharmacological treatments, such as selective hormone modulators, and minimally invasive techniques, such as fibroid embolization and laparoscopic excision of endometriosis. Integrating personalized strategies into care allows for better clinical outcomes and greater patient well-being.